Optimization of Specific PCR Conditions for Cows (Bos taurus) in Rendang Samples for Molecular-Based Halal Tests - Nurfadillatun Nisa Wijaya; Sisca Alicia Farma; Dwi Hilda Putri; Afifatul Achyar (Tropical Genetics, 2022)
Rendang is one of the popular foods in Indonesia made from beef as the main ingredient, which has great potential in tourism development. As a country that has a Muslim majority population, this is very influential for the halal tourism industry. Halal tourism is the parent of tourism in accordance with Islamic principles. The issue of halal food is a sensitive issue for the community. The rise of mixing of non-halal ingredients such as pork in processed food products has worried the public, especially for adherents of the Islamic religion. However, this can be detected molecularly using the Polymerase Chain Reaction (PCR) technique which will amplify the DNA of the target gene of the species to be identified. Each gene has a primer with a different concentration and annealing temperature, so that prior to PCR with research samples, it is necessary to optimize the primer concentration and annealing temperature in order to obtain the appropriate PCR composition and conditions so as to obtain optimal PCR results. In this study, optimization of bovine-specific BOS primers that amplify the ND5 gene in mitochondrial DNA was carried out, namely ND5 (NADH dehydrogenase subunit 5). The results showed that the optimum annealing temperature was 48.2ºC, the optimum primary concentration was 0.5 μM.